2003
DOI: 10.1093/jnci/95.13.981
|View full text |Cite
|
Sign up to set email alerts
|

National Practice Patterns and Time Trends in Androgen Ablation for Localized Prostate Cancer

Abstract: Rates of both PADT and NADT are increasing across risk groups and treatment types. Future clinical trials must define more clearly the appropriate role of hormonal therapy in localized prostate cancer, and their results should shape updated practice guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
220
1
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(228 citation statements)
references
References 32 publications
4
220
1
3
Order By: Relevance
“…Given that over 200,000 men are diagnosed with prostate cancer annually, 9 of which approximately half are treated with radical prostatectomy, 10 and a third of which will experience a PSA recurrence after surgery, 11 the need for accurate prognostic markers in this setting is great. PSADT following biochemical recurrence after radical prostatectomy is an excellent prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…Given that over 200,000 men are diagnosed with prostate cancer annually, 9 of which approximately half are treated with radical prostatectomy, 10 and a third of which will experience a PSA recurrence after surgery, 11 the need for accurate prognostic markers in this setting is great. PSADT following biochemical recurrence after radical prostatectomy is an excellent prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…This earlier detection and downward stage migration has been accompanied by a proliferation of treatment alternatives, including its use as neoadjuvant or adjuvant therapy for surgery and radiotherapy, for biochemical relapse after surgery or radiation, and even as primary therapy for non-metastatic disease. 5 It appears now that patients are given androgen deprivation therapy (ADT) based on their PSA and not necessarily the presence of clinical symptoms, and they are likely to be on ADT for longer periods than in the past. The expansion of ADT has been most dramatic with external beam radiotherapy, i.e., from 9.8% to 74.6%.…”
Section: Introductionmentioning
confidence: 99%
“…The expansion of ADT has been most dramatic with external beam radiotherapy, i.e., from 9.8% to 74.6%. 5 In addition, the use of long-term neoadjuvant ADT (up to 3 years in combination with radiation therapy for highrisk PCa) will result in permanent castration to some men. Overall, it has been estimated that approximately 50% of PCa patients treated in industrialized nations will receive ADT at some point in their disease course.…”
Section: Introductionmentioning
confidence: 99%
“…However, as use of ADT becomes more widespread, evaluation of the potential adverse effects associated with this treatment is imperative for treatment decision making and for ameliorating the impact of therapy on survivors' quality of life. [8][9][10][11][12] Major adverse effects of ADT that are attributed to decrease in estrogen levels include hot flashes and loss of libido. 10 Furthermore, numerous studies reported association of ADT with fatigue, decrease in bone mass, higher percentage of body fat, decrease in lean muscle mass, and increased incidence of fractures.…”
mentioning
confidence: 99%